2007
DOI: 10.1136/gut.2007.131607
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of interferon-induced depression in chronic hepatitis C with citalopram: a randomised, double-blind, placebo-controlled study

Abstract: The findings demonstrate clearly that citalopram treatment is highly effective in HCV patients on interferon therapy, when initiated after the onset of clinically relevant depressive symptoms. This suggests that a general SSRI prophylaxis is not necessary in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0
13

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 31 publications
1
75
0
13
Order By: Relevance
“…Although prophylaxis of IFN-induced depression with antidepressants remains controversial, 22 pharmacological treatment of depression after its onset has proven effective and beneficial. 3,23 concluSIonS…”
Section: Resultsmentioning
confidence: 99%
“…Although prophylaxis of IFN-induced depression with antidepressants remains controversial, 22 pharmacological treatment of depression after its onset has proven effective and beneficial. 3,23 concluSIonS…”
Section: Resultsmentioning
confidence: 99%
“…35 Kraus et al demonstrated in a randomised, placebo-controlled trial, that 20 mg citalopram daily was significantly superior to placebo in reducing interferon-related depressive symptoms after 2 and 4 weeks. 92 A significant improvement in major depression was found in interferon-treated HCV patients managed concomitantly with 20 mg paroxetine, 93 allowing 79% of the subjects who had developed depression to complete interferon treatment. Certainly, SSRI use in chronic HCV patients does not appear to have any additional adverse effects in most case series and trials.…”
mentioning
confidence: 99%
“…С другой стороны, в современной литературе широко обсужда-ется феномен «цитокин-индуцированной депрессии» (Kalyoncu O.A., 2005;Pace T., 2007;Beckwith A.R., 2008;Kraus M.R., 2008;Schaefer M., 2008). Рост уровня биомаркеров воспаления (в частности, ИЛ-6) кор-релирует с депрессивными симптомами, а применение цитокиновой терапии сопровождается симптомами усталости, анергии (Miller A.H., Raison C.L., 2008).…”
Section: иммунологические подходы к оптимизации терапии депрессивных unclassified
“…2.4, в литературе широко обсуждается феномен «цитокин-индуцированной депрессии» (Kalyoncu O.A. et al, 2005;Pace T. et al, 2007;Beckwith A.R., 2008;Kraus M.R. et al, 2008;Schaefer M. et al, 2008).…”
Section: возможность применения сверхмалых доз антител в комплексной unclassified